Working and Living conditions of Chinese migrants in Mauritius (Global Journal of Human-Social Science, 2011)
Chinese migrants are well known for being courageous patient hardworking and change competent Their work culture is well recognised in Mauritius They come to Mauritius with the intent of working hard and saving money for their families back home They make the least amount of complaints and adapt very quickly to changing conditions of work Through their contributions during the last three decades in various sectors of the economy more particularly in the Export Processing Zone EPZ it can be safely assumed that they have helped much towards the development of the country The main objectives of this paper are to i take stock of the working and living conditions of the Chinese expatriates and ii examine the extent to which they are satisfied with their work For the purpose of this study 50 Chinese workers have been interviewed One of the main findings of this study is that the majority of Chinese migrants are often exploited in various ways by their employers Quite a large number of the respondents argued that they were victims of discrimination in the country One main recommendation would be to review the conditions of contract workers regarding their safety and security The host country should take the responsibility of ensuring that new policies devised are translated into effective actions for the benefit of the expatriates
Keywords: Chinese migrants; work culture; living conditions; working conditions and discrimination